2016
DOI: 10.1055/s-0035-1569342
|View full text |Cite
|
Sign up to set email alerts
|

Initial Weekly HRV Response is Related to the Prospective Change in VO2max in Female Soccer Players

Abstract: The aim of this study was to determine whether the early response in weekly measures of HRV, when derived from a smartphone application, were related to the eventual change in VO2max following an off-season training program in female soccer athletes. 9 female collegiate soccer players participated in an 11-week off-season conditioning program. In the week immediately before and after the training program, each participant performed a test on a treadmill to determine maximal oxygen consumption (VO2max). Daily m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 30 publications
1
35
0
Order By: Relevance
“…For example, participants completing cancer treatment more recently may experience greater variability and therefore using an isolated daily HRV measurement as in the present study may have confounded the results. Therefore, future research investigating the effects of exercise training on HRV among cancer survivors may complete more robust HRV analyses including weekly coefficients of variation as performed in athlete monitoring investigations 37 to account for the high variability in recent cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, participants completing cancer treatment more recently may experience greater variability and therefore using an isolated daily HRV measurement as in the present study may have confounded the results. Therefore, future research investigating the effects of exercise training on HRV among cancer survivors may complete more robust HRV analyses including weekly coefficients of variation as performed in athlete monitoring investigations 37 to account for the high variability in recent cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, Flatt & Esco [ 24 ] performed the RR recordings in a laboratory with controlled settings (quiet, dimly lit, controlled temperature and humidity) which are prerequisites for obtaining a valid HRV analysis [ 35 ]. However, regular HRV analysis in athletes is often performed at home for logistical reasons and we followed the RR recording procedure used in other recent studies [ 5 , 6 , 8 , 13 ]. Based on the current authors’ experience, RR recordings performed at home may not be as well standardized as those performed in laboratory environment.…”
Section: Discussionmentioning
confidence: 99%
“…However, the 30 s required to stabilize the HR was not sufficient to stabilize the Ln RMSSD. For example, the ithlete mobile HRV application uses an algorithm to start recording Ln RMSSD based on detecting a stable HR [ 5 ]. It is questionable whether this is an accurate approach, because the present study showed that HR stabilizes earlier than Ln RMSSD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The week-to-week responses in RMSSD MEAN may be mostly related to longitudinal changes in aerobic fitness rather than improvements in muscular performance by long-term resistance training [32,33,34,35,36]. For instance, Esco et al showed that the initial change in RMSSD MEAN from weeks 1 to 3 of an 11-week conditioning program was strongly related to the adaptation of maximal oxygen consumption in female soccer player [37]. Though maximal oxygen consumption was not accounted for in the case study, future research should analyze the impact of aerobic fitness on muscle performance recovery and HRV responses in resistance trained athletes.…”
Section: Discussionmentioning
confidence: 99%